STRATEGIES FOR STRENGTHENING SOCIAL BONDING IN A FOREST FARMER GROUP: AN FFA AND AHP APPROACH - Wijayanti, Andi Ridha Yayank; Sila, Sri Arfiani Rahim; Zamzam, Nur; Saharuddin, Saharuddin; Supratman, Supratman; Arafat, Andi (Gorontalo Journal of Forestry Research, 2025)
Strengthening social bonding within forest farmer group institutions is essential for the sustainability of community-based forest management. This study aims to formulate strategies for strengthening social bonding by identifying its driving and restraining factors. Data were collected through observation, in-depth interviews, and expert assessments. The analysis integrated Force Field Analysis (FFA) to map drivers and barriers, and the Analytic Hierarchy Process (AHP), based one expert Assessments, to prioritize these factors. The results show that leadership legitimacy, a culture of mutual cooperation, conservation awareness, active participation, and strong social networks are the main driving factors. Prominent constraints include leadership centralization, unequal member contributions, undocumented norms, technical capacity gaps, and limited external networks. Strengthening strategies include leadership distribution, reinforcement of collective activities, documentation of norms and values, enhancement of technical capacity, and expansion of external networks. These findings provide an evidence-based framework for strengthening social capital and supporting the institutional sustainability of forest farmer groups.